PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA GURU YANG DIMODERASI OLEH IKLIM SEKOLAH DI MTS SEKECAMATAN WINONG KABUPATEN PATI - Suyati, 12.5202.0216; Suhari, Yohannes (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to examine the effect of transformational leadership and motivation to work on the performance of teachers in MTs Sekecamatan Winong Pati regency with school climate moderated. The specific objectives of this study was to examine the effect of transformational leadership and motivation to work on teacher performance that dmoderasi by climatic role. The usefulness of this study is to clarify and extend previous research on the effect of transformational leadership and motivation to work on teacher performance are moderated school climate. This study used a population of teachers in MTs Sekecamatan Winong Pati regency much as 121 teachers. Sampling techniques in this study is nonprobability sampling with purposive sampling method. Based on the results of the study can be summarized as follows:Â  Â transformational leadership influence on teacher performance, motivation does not affect the performance of teachers, school climate affect the performance of the teacher, the influence of transformational leadership on teacher performance is moderated by school climate, and the effect on the performance of teachers work motivation is not moderated by school climate. Keywords: transformational leadership, motivation, school climate, teacher performance.